Edukasi Gosok Gigi yang Baik dan Benar Untuk Anak Balita - Khayati, Yulia Nur; Windayanti, Hapsari; Dewi, Maya Kurnia; Andaeni, Wahyu Retno; Putri, Alif’fah Setiyana; Rahmadini, Ameliana Friskia; Ananda, Ayu; Hawa, Christania R.L (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2020)
Because of its importance, teaching children to brush their teeth properly is necessary to do since their childhood. Wrong behavior in brushing teeth can affect teeth and mouth’s health such as causing dental caries (Wiradona, 2013). Recently, many schools in Indonesia have already given the education about how to brush teeth properly through the program of School Health Dental Unit (UKGS) since 1951 (Kemenkes, 2012). One of the reasons to do this community empowerment was because there were children who were still reluctant to brush their teeth. It happened because their parents had lack knowledge about how to teach their children to brush teeth properly. To overcome this, the education about how to brush teeth properly was given by using leaflet and video given to the parents so that they could teach their children to do this, therefore the prevalence of dental caries in children could be reduced. After getting the education about how to brush teeth properly, it showed a significant increase of the knowledge indicating by the initial average value of 50 increasing to 95.AbtrakPentingnya perilaku menyikat gigi dengan benar haruslah diajarkan sejak dini, karena perilaku menyikat gigi yang salah akan berdampak terhadap kesehatan gigi dan mulut seseorang, salah satu dampak yang ditimbulkan adalah karies gigi (Wiradona, 2013). Saat ini sekolah-sekolah di Indonesia sudah memberikan pendidikan mengenai cara menyikat gigi melalui program UKGS yang sudah berjalan sejak tahun 1951 (Kemenkes, 2012). Salah satu alasan dilakukan pengabdian masyarakat ini karena masih ditemukan anak yang malas untuk menggosok gigi. Hal ini disebabkan karena orang tua belum tau caranya mengajarkan menggosok gigi pada anak. Untuk mengatasi masalah tersebut dilakukan pemberian edukasi cara menggosok gigi yang benar dengan media leaflet dan video yang diberikan kepada orang tua agar dapat mengajarkan anaknya cara menggosok gigi yang benar sehingga prevalensi karies pada anak akan terus menurun. Setelah diberikan penyuluhan tentang menggosok gigi yang benar terdapat peningkatan pengetahuan yang cukup signifikan yaitu dari nilai rata-rata 50 meningkat menjadi 95 setelah diberikan penyuluhan.